2015
DOI: 10.1038/icb.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

GM‐CSF and uPA are required for Porphyromonas gingivalis‐induced alveolar bone loss in a mouse periodontitis model

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) and urokinase-type plasminogen activator (uPA) can contribute to the progression of chronic inflammatory diseases with possible involvement of macrophages. In this study, we investigated the role of both GM-CSF and uPA in Porphyromonas gingivalis-induced experimental periodontitis using GM-CSF-/- and uPA-/- mice. Intra-oral inoculation of wild-type (WT) C57BL/6 mice with P. gingivalis resulted in establishment of the pathogen in plaque and a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 102 publications
1
21
0
Order By: Relevance
“…Activation of the complement cascade has been invoked as a key aspect of the role of P. gingivalis as a keystone pathogen (20). Similar to the findings in the C5aR Ϫ/Ϫ mice, which are resistant to P. gingivalis colonization and are thus protected from alveolar bone loss (53), we recently found that P. gingivalis poorly colonized the subgingival plaque in uPA Ϫ/Ϫ mice compared with wild-type mice (29). This likely explains the protection of uPA Ϫ/Ϫ mice from P. gingivalis-induced alveolar bone loss but also suggests that the pathogen depends on uPA to colonize the host and drive inflammation.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Activation of the complement cascade has been invoked as a key aspect of the role of P. gingivalis as a keystone pathogen (20). Similar to the findings in the C5aR Ϫ/Ϫ mice, which are resistant to P. gingivalis colonization and are thus protected from alveolar bone loss (53), we recently found that P. gingivalis poorly colonized the subgingival plaque in uPA Ϫ/Ϫ mice compared with wild-type mice (29). This likely explains the protection of uPA Ϫ/Ϫ mice from P. gingivalis-induced alveolar bone loss but also suggests that the pathogen depends on uPA to colonize the host and drive inflammation.…”
Section: Discussionsupporting
confidence: 68%
“…In the case of pro-uPA, the RgpAKgp complex cleaved at the major consensus sites (Lys Much of the damage to the periodontal tissue in PD is now recognized to be caused by the destructive host inflammatory response (41). We have shown that macrophages (31) and uPA (29) are important in the P. gingivalis-induced PD model. Interestingly, protection of uPA Ϫ/Ϫ mice in the P. gingivalis-induced PD model was associated with reduced numbers of macrophages in the gingival tissue (29), consistent with our data showing a critical role for uPA in promoting macrophage adhesion and motility (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations